INTERNAL CONTROL SYSTEMS IN MODERN AND BIBLICAL PERSPECTIVES: PREVENTING FINANCIAL FRAUD AT THE X CHURCH IN EAST JAVA - Eunike Rhema Yohanna; Sri Pujiningsih; Dodik Juliardi (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
This study aimed to determine the practice of internal control in modern and biblical perspectives in terms ofminimizing irregularities and financial abuse at the X Church in East Java. This study used a qualitative (nonpositivistic) approach by the type of case study research. Data collection was carried out by observation andinterviews with the church pastor, treasurer, the Treasury Supervisory Agency (BPP) team, and churchcongregations to get information about the control system in X church. Data analysis in this study used a single sitedata model. The results of this study indicate that the practice of internal control systems in a modern perspective(COSO) at X church has not fully implemented the five components of the internal control system according toCOSO because it assumes that the church is a religious organization that does not have rigid regulations such asprofit-seeking organizations. So that it becomes a reproach for the church treasurer to commit fraud against thechurch. In addition, the internal control system in the Biblical perspective of X church found that church had applieda dual custody system and organizational ethical values taken from the Bible to be used as a foundation in servingGod, but in reality, the church treasurers abuse their power or authority and act not in accordance with God's word.The theoretical contribution to this research is to contribute to strengthening and enriching the theory of trianglefraud and the practical contribution of this research can be used as knowledge so that the church can improve theexisting internal control system to minimize financial abuse in the church.